2020
DOI: 10.1111/jpc.15065
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 in human milk is inactivated by Holder pasteurisation but not cold storage

Abstract: Aim As the COVID‐19 pandemic evolves, human milk banks world‐wide continue to provide donor human milk to vulnerable infants who lack access to mother's own milk. Under these circumstances, ensuring the safety of donor human milk is paramount, as the risk of vertical transmission of SARS‐CoV‐2 is not fully understood. Here, we investigate the inactivation of SARS‐CoV‐2 in human milk by pasteurisation and the stability of SARS‐CoV‐2 in human milk under cold storage. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0
7

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 10 publications
5
30
0
7
Order By: Relevance
“…explored the efficiency of holder pasteurization against SARS-CoV-2 in 5 milk samples and found that infectivity of all 5 tested SARS-CoV-2 isolates is completely eliminated by this treatment. This confirms studies where holder pasteurization of milk spiked with three early SARS-CoV-2 isolates prevented viral infection of monkey derived Vero cells[7][8][9] . We verify the efficiency of holder pasteurization upon inclusion of additional viral strains, encompassing the dominant pandemic variant D614G that shows increased fitness in cell culture (Netherlands/01, UKEssen) 10 as well as highly susceptible human Caco-2 cells that express the viral entry factor transmembrane serine protease 2 (TMPRSS2).…”
supporting
confidence: 84%
“…explored the efficiency of holder pasteurization against SARS-CoV-2 in 5 milk samples and found that infectivity of all 5 tested SARS-CoV-2 isolates is completely eliminated by this treatment. This confirms studies where holder pasteurization of milk spiked with three early SARS-CoV-2 isolates prevented viral infection of monkey derived Vero cells[7][8][9] . We verify the efficiency of holder pasteurization upon inclusion of additional viral strains, encompassing the dominant pandemic variant D614G that shows increased fitness in cell culture (Netherlands/01, UKEssen) 10 as well as highly susceptible human Caco-2 cells that express the viral entry factor transmembrane serine protease 2 (TMPRSS2).…”
supporting
confidence: 84%
“…At present, the World Health Organization (WHO) recommends that breastfeeding women with suspected or confirmed SARS-COV-2 infection be encouraged to continue breastfeeding as the benefits outweigh the risks [ 13 ]. Holder pasteurization has been shown to eradicate viruses from breastmilk, including SARS-CoV-2 virus [ 3 , 14 ]. Our results show that whilst it does not affect antibody levels in either serum or breastmilk, it decreased the neutralizing capacity of breastmilk SARS-CoV-2 antibodies whilst having no negative effect on serum SARS-CoV-2 neutralization.…”
Section: Discussionmentioning
confidence: 99%
“…20 μL of each dilution was then added to cells seeded a day prior at 3×10 3 cells in a volume of 40 μL of MEM-2% FCS per well in a 384-well plate (Corning #CLS3985). The plates containing the cells and compounds were incubated for 30 minutes at 37 °C, 5% CO 2 following which 20 μL of virus solution at 8×10 3 TCID50/mL ( 63 ) was added to the wells. Plates were incubated at 37 °C, 5% CO 2 for a further 72 hours following which the cells were stained with NucBlue dye (Invitrogen, #R37605) according to manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%